1995
DOI: 10.1038/nbt0495-389
|View full text |Cite
|
Sign up to set email alerts
|

Production of Recombinant Proteins in Chinese Hamster Ovary Cells Using A Protein-Free Cell Culture Medium

Abstract: The growth-factor prototrophic Chinese hamster ovary (CHO) SSF3 cell line was previously adapted for growth in serum-free media. Here we present a newly designed medium which allows these cells to grow in the absence of any exogenously added growth factors. To investigate the capacity of CHO SSF3 cells for the efficient production of recombinant proteins in protein-free media, expression plasmids containing either a human single chain urokinase-type plasminogen activator (uPA)-encoding cDNA or a humanized immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…Experiments similar to those described above for the serumfree medium formulation revealed that generation times are significantly increased in the protein-free formulation for cell lines CHO DUKXB11, CHO-A11-A2, and CHO-A11-A279 when compared to the serum-free formulation (Table 5). However, they are comparable with generation times reported for CHO SSF3 cells producing urokinase-type plasminogen activator (about 27 h, Zang et al, 1995) or a humanized immunoglobin G kappa light chain (about 15 h, Zang et al, 1995). The increased generation times in the protein-free medium are probably due to a lack of insulin and indicate a partial block in progression through the cell cycle, presumably a prolongation of the G1-phase.…”
Section: Growth Characteristics and Atiii Secretion In Protein-free Msupporting
confidence: 62%
See 1 more Smart Citation
“…Experiments similar to those described above for the serumfree medium formulation revealed that generation times are significantly increased in the protein-free formulation for cell lines CHO DUKXB11, CHO-A11-A2, and CHO-A11-A279 when compared to the serum-free formulation (Table 5). However, they are comparable with generation times reported for CHO SSF3 cells producing urokinase-type plasminogen activator (about 27 h, Zang et al, 1995) or a humanized immunoglobin G kappa light chain (about 15 h, Zang et al, 1995). The increased generation times in the protein-free medium are probably due to a lack of insulin and indicate a partial block in progression through the cell cycle, presumably a prolongation of the G1-phase.…”
Section: Growth Characteristics and Atiii Secretion In Protein-free Msupporting
confidence: 62%
“…CHO SSF3, were selected from DUKXB11 cells by replacing part of the medium every week . A protein-free medium for CHO SSF3 cells was described (Zang et al, 1995). In addition, a cell line preadapted to serum-free conditions, derived from DUKXB11 cells was described (Sinacore et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It was not necessary to use protease inhibitors in the medium or to include an additional purification step to eliminate the enzyrnatically active form. The highest levels of production of this and other recombinant proteins obtained with stably transfected SSF3-derived cell lines were, like observed with the parental CHO(dhfr-)-derived cells, around 20 50/zg per 10 6 cells day -1 or 2-5 10 t4 molecules cell -1 day ~ [23]. The availability of procedures to manipulate mammalian cells genetically in the absence of serum also opens the possibility of using these cells for other experiments than production of recombinant proteins, where serum-containing medium would interfere, for example in assays of signal transduction by hormones naturally present in serum.…”
Section: Prospects For Animal Cell Culture In Protein-free Mediamentioning
confidence: 61%
“…However, secretion of uPA by yeast was hampered due to the formation of large aggregates in the endoplasmic reticulum (Agaphonov et al 2002). Zang and colleagues have previously explored the use of a mammalian expression system to avoid complications observed with prokaryotic or yeast systems (Zang et al 1995). Using normal, wild type CHO cells, they were able to generate reasonable quantities of recombinant uPA, however it was not reported in this study if the recombinant uPA was proteolytically active or structurally comparable to native uPA.…”
Section: Discussionmentioning
confidence: 92%
“…Expression of recombinant human uPA has been attempted using bacterial Lenich et al 1992;Wang et al 2000), yeast (Agaphonov et al 2002), and mammalian (Zang et al 1995) expression systems with mixed results. In many cases, recombinant protein yields are low and/or post-translational modifications are missing or aberrant.…”
Section: Introductionmentioning
confidence: 99%